A Remark on the Jurisdiction of the Fair Housing Act over Racial Discrimination in Housing Platforms - Melita Noemi Odell (Studies in Law and Justice, 2023)
This paper critically examines the jurisdiction of the Fair Housing Act in addressing racial discrimination within housing platforms. The study explores the Act’s jurisdiction, its scope, applicability, and interpretations, analyzing legal precedents and controversies. The paper engages with critiques and debates surrounding the Act, considering limitations in addressing discrimination and proposed amendments. It assesses the implications for future enforcement, addressing emerging challenges and offering potential reforms and policy recommendations.